Eruptions that shook the world - Oppenheimer, Clive (Cambridge, UK ; New York : Cambridge University Press, 2011)
"What does it take for a volcanic eruption to really shake the world? Did volcanic eruptions extinguish the dinosaurs, or help humans to evolve, only to decimate their populations with a super-eruption 73,000 years ago? Did they contribute to the ebb and flow of ancient empires, the French Revolution and the rise of fascism in Europe in the 19th century? These are some of the claims made for volcanic cataclysm. Volcanologist Clive Oppenheimer explores rich geological, historical, archaeological and palaeoenvironmental records (such as ice cores and tree rings) to tell the stories behind some of the greatest volcanic events of the past quarter of a billion years. He shows how a forensic approach to volcanology reveals the richness and complexity behind cause and effect, and argues that important lessons for future catastrophe risk management can be drawn from understanding events that took place even at the dawn of human origins"--
"Fire & brimstone: how volcanoes work 'Some volcanos are in a state of incessant eruption; some, on the contrary, remain for centuries in a condition of total outward inertness, and return again to the same state of apparent extinction after a single vivid eruption of short duration; while others exhibit an infinite variety of phases intermediate between the extreme of vivacity and sluggishness.' [1RFA-001] The Earth is cooling down! This has nothing to do with contemporary global warming of the atmosphere and surface. I refer instead to the Earth's interior - the source of the molten rocks erupted by volcanoes throughout the planet's 4.567 billion year history"--
Includes bibliographical references and index.
Keywords: Volcanism; Volcanism; Volcanology